1998
DOI: 10.1128/iai.66.7.3255-3263.1998
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Epithelial Cell-Derived Histone H1 Proteins in Innate Antimicrobial Defense in the Human Gastrointestinal Tract

Abstract: In the human gastrointestinal tract, microorganisms are present in large numbers in the colon but are sparse in the proximal small intestine. In this study, we have shown that acid extracts of fresh human terminal ileal mucosal samples mediate antimicrobial activity. Following cation-exchange chromatography, one of the eluted fractions demonstrated antibacterial activity against bacteria normally resident in the human colonic lumen. This activity was further fractionated by reverse-phase high-performance liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
66
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(71 citation statements)
references
References 33 publications
2
66
0
3
Order By: Relevance
“…Hence, ongoing analyses in our laboratories involve studies of antimicrobial and laminin-containing heparin-binding peptide fractions derived from human basement membranes, as well as characterization of heparin-binding peptides generated by proteolytic cleavage of human complement factor C3 and other plasma proteins. [15] and the reported antibacterial protein human histone H1B [28] (upper). Homology is also found between another heparin-binding motif (TXXBXX TBXXXTBB) [12,14] and the known antibacterial peptide dermaseptin [29] from the two-coloured leaf frog 1 (lower).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, ongoing analyses in our laboratories involve studies of antimicrobial and laminin-containing heparin-binding peptide fractions derived from human basement membranes, as well as characterization of heparin-binding peptides generated by proteolytic cleavage of human complement factor C3 and other plasma proteins. [15] and the reported antibacterial protein human histone H1B [28] (upper). Homology is also found between another heparin-binding motif (TXXBXX TBXXXTBB) [12,14] and the known antibacterial peptide dermaseptin [29] from the two-coloured leaf frog 1 (lower).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that histones have additional functions, including hormone activity [25], activation of leucocytes in salmon [26] and as part of the antimicrobial defence in mammals [27][28][29]. Even if the antimicrobial effect of histones has been known for decades [30], they were just recently linked to the innate immune system of frog [31], fish [2,3,15,16,[32][33][34][35][36] and mammals [29,37,38]. In the study by Robinette et al [15], a histone 2B-like protein was shown to inhibit important bacterial and fungal pathogens of fish, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These complexes have been named neutrophil extracellular traps and are highly bactericidal. By using immunohistochemical analysis, it was reported that histone H1 in human terminal ileal mucosa is not only localized to the nucleus but also in the cytoplasm [29]. Histones H2A and H2B were also shown to be present in the cytoplasm of syncytiotrophoblasts and amnion epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Their inhibitory potencies in E. coli (LD 50 : 3.48 and 4.34 lgAEmL )1 ) are comparable to that of the antimicrobial peptide LL-37 (LD 50 : 4.10 lgAEmL )1 ). The antimicrobial activities of H4-(86-100) and HNr depend upon the integrity of the molecules, as precursors [H4-(84-102), pro-HNr] and fragments [bovine histogranin (HNb)-(1-13), HNb- (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), H4-(89-102) or OGP] are at least five times less potent than the parent peptides. Among various HN-like compounds, cyclo-(-Gly-pCl-Phe-Tyr-d-Arg) (compound 3) and N-5-guanidino pentanamide-(2R)-yl-2-N-(p-hydroxyphenylacetyl)-4-(p-chlorobenzoyl)-phenylene diamine (compound 8) display antimicrobial activities comparable to that of HNr.…”
mentioning
confidence: 99%